Optimalisasi Kinerja Alat Pirolisis pada Pembuatan Biochar dari Limbah Jengkok Tembakau - Hendra Banat; Sinar Perbawani Abrina Anggraini; Yeni Ulfi Rahayu; Taufik Iskandar (Universitas Tribhuwana Tunggadewi Malang, 2018)
The pyrolysis process can convert biomass waste from various agricultural wastes into high value products, easy to operate, friendly of high environmental security standard and environment. This research aims to determine the optimization of pyrolysis machine performance based on temperature and combustion time in producing quality biochar. Variable pyrolisis temperature are (400, 450, 500, 550, 600) 0C with combustion time (30, 35, 40) minutes and type of biomass waste in the form of tobacco waste. Tobacco waste is the remnants of the production process of cigarettes in the form of fine (powder), put in a sack or burlap and stored in certain warehouses to avoid undesirable things to the environment. Pursuant to result of research which have been done, the optimal performance of pyrolysis machine is at 500 °C and 30 minutes with biochar moisture content of 0,06%, biochar percentage 29,79%, loss components of 70,21%, heat loss of 304,50 KJ / Kg and machine performance of 17,06 Kg / m.h. So that can be concluded that a pyrolysis machine can be said to be optimal if the machine produces biochar with low moisture content, high biochar percentage (yield percentage), low loss components, low discharged energy and produce high machine performance with the lowest possible time.